Wolność wypowiedzi prasowej a zniewaga - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The crime of using insulting language protects human dignity (its external aspect) from such infringements that in terms of culturally determined and commonly accepted standards express contempt for an individual, irrespective of his or her feelings. The offence of using insulting or offensive language, refers to an act of disparagement, or offensive behavior towards somebody. An insult expressed via the mass media results in more serious consequences. The public nature of an act referred to in Art. 216, section 1 of Penal Code means that it was committed in a manner allowing it to be noted by a number of people that cannot be determined in advance. Therefore, a qualified type of insult involves one committed via the mass media. The ratio legis of this construction is rather obvious, as an insult committed via the mass media has a larger range, and a larger impact area.